Urban life stress in preadolescents: a longitudinal assessment in Lima - Casuso, Liliana (2013)
This study has the aim to longitudinally explore stressors and perceived stress in several domains in preadolescents in the urban area of Lima. A non-clinical sample (N = 170, 9-11 years) from low and high socioeconomic status (SES) was investigated in four waves of data collection across two subsequent years. A multilevel analysis revealed that the intensity of perceived life stress decreased across the two years. Results further showed that preadolescents from low SES were more stressed about themselves and family than those from high SES. Regarding gender, girls were more stressed about their family and friends than boys. Finally, a list of the most frequent stressors in preadolescents living in the urban area of Lima is described.